THE DEVELOPMENT OF MATHEMATIC LEARNING INSTRUMENTS MODEL DISCOVERY LEARNING IN THE QUADRILATERAL AND TRIANGLE TOPIC TO FACILITATE THE MATHEMATICAL REPRESENTATION STUDENTS ABILITIES FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Devi Rahayu; Kartini Kartini; Putri Yuanita (AXIOM : Jurnal Pendidikan dan Matematika, 2021)
Abstrak:Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran matematika berupa Silabus, Rencana Pelaksanaan Pembelajaran (RPP) dan Lembar Aktivitas Siswa (LAS) model discovery learning pada materi segiempat dan segitiga untuk memfasilitasi kemampuan representasi matematis siswa SMP/MTs yang valid dan memenuhi syarat praktikalitas. Model penelitian pengembangan yang digunakan adalah model 4-D yang terdiri dari tahap define (pendefenisian), design (perancangan), develop (pengembangan), dan disseminate (penyebaran). Uji coba terbatas dilakukan di SMP Negeri 5 Tapung Hilir. Hasil penelitian menunjukkan bahwa hasil validasi perangkat pembelajaran memiliki skor ≥ 2,5 dengan kategori valid, dan hasil praktikalitas memiliki persentasi skor 87%. Sehingga perangkat pembelajaran discovery learning pada materi segiempat dan segitiga untuk memfasilitasi kemampuan representasi matematis siswa kelas VII SMP/MTs telah valid dan memenuhi syarat praktikalitas. Kata Kunci:Penelitian Pengembangan, Perangkat Pembelajaran, Discovery Learning, Model Pengembangan 4-D, Kemampuan Representasi matematis Abstract:This research aims to produce the mathematics learning instruments which includes syllabus, learning implementation plans (RPP) and student activity sheets (LAS) model discovery learning on the material of quadrilateral and triangles to facilitate SMP/MTs students the mathematical representation abilities of that are valid and qualified of the practicality. The development research model used is the 4-D which consists the stages of define, design, develop, and disseminate. The limited trial was conducted at SMP Negeri 5 Tapung Hilir. The results showed that the result of learning instruments validation of had a score of ≥ 2.5 in the valid category, and the results of practicality had a percentage score of 87%. So that the instruments discovery learning on the material of quadrilateral and triangles to facilitate SMP/MTs of seventh grade students the mathematical representation abilities that are valid and qualified of the practicality. Keywords:Development Research, Learning Instruments, Discovery Learning, 4-D Development Models, Mathematical Representation Ability